Implementasi PERMENDIKBUD No. 14 Tahun 2018 terhadap Peneriman Peserta Didik Baru Berdasarkan Zonasi Sekolah - Ni Komang Rai Widhyaningsih; I Wayan Arthanaya; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Education is something that is important can provide knowledge that can improve the characteristics of life, both in personal life, community life, and state life. A New Student Admission, often referred to as PPDB, isan annual activity which is the selection stages for prospective new students organized by school-level committees under the supervision and coordination of the Office of Education. This year, PPDB uses a new system, the zoning system, which aims to equalize students. The purpose of this study was to describe how the implementation of Permendikbud number 14 in 2018 and what are the factors inhibiting the implementation of Permendikbud number 14 in 2018 on the admission of new students based on zoning. This research was designed using an empirical legal research approach. The results of this study indicated that the implementation of Permendikbud No. 14 of 2018 in High Schools / Kejuraan especially in the South Kuta area has not been running effectively because there was one school that received protests from students' parents which resulted in the process of hiring new students being hindered. In addition, this study also showed that the inhibiting factors for the implementation of Permendikbud No. 14 of 2018 on the admission of new students based on zoning consisted of internal factors, namely the committee was less selective in examining student requirements and the application provided was experiencing interference, and external factors namely location, community mainset, and domicile certificate.